Direct Synthesis of Unsymmetrical Dithioacetals - Bognar, Sabine (Chemistry, 2021)
Dithioacetals are a frequently used motif in synthetic organic chemistry and have recently seen increasing attention as structural motif in promising antiviral agents against plant pathogens. Most existing reports, however, only discuss symmetrical dithioacetals. Examples of mixed dithioacetals are scarce and no general method for the selective synthesis of these compounds exists. Herein, a synthetically simple general one‐step protocol was developed for the synthesis of a broad range of unsymmetrical dithioacetals consisting of one aromatic and one aliphatic thiol moiety from the corresponding aldehyde/thiol mixture. The mixed S,S‐acetals were obtained in high yields, and a great variety of functional groups was tolerated. Kinetic control enabled an excellent selectivity in regard to the unsymmetrical dithioacetal.